Bovine trypanosome prevalence at game/livestock interface of Hluhluwe-Umfolozi Game Reserve in Kwazulu-Natal Province, South Africa - Latif, Abdalla A. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.